Meta Analisis Pengaruh Pembelajaran Inkuiri Terhadap Keterampilan Proses Sains - Muhammad Salim; Abdul Salam; Dewi Dewantara (Indonesian Publication Center, 2022)
This meta-analysis aims to determine the magnitude of the effect size exerted by the inquiry-based learning model on students' science process skills in Indonesia through a systematic statistical analysis of relevant literature. The results demonstrate that the inquiry model exerts a significant influence, with a combined effect size of 1.030, categorized as a large effect on the enhancement of science process skills. The effectiveness of this model varies according to supporting characteristics; the senior high school (SMA) level exhibits the most dominant influence with a value of 1.473, while, in terms of learning topics, unspecified materials contribute the highest influence with a value of 2.35. Overall, these findings conclude that the inquiry-based learning model proves to have a substantial positive impact on the development of students' science process skills.